515 Serious Illness Communication Practices in Glioblastoma Care: An Institutional Perspective. (1st April 2022) - Miranda, Stephen; Reed-Guy, Lauren; Alexander, Tyler; Biggiani, Gregory; Grady, M. Sean; Jones, Joshua; Bagley, Stephen; Kumar, Pallavi; O'Connor, Nina
Abstract : INTRODUCTION: Serious illness (SI) communication about goals, prognosis, and advance care planning is essential for supporting goal-concordant care among glioblastoma patients, however clinicians may fail to elicit patients' preferences while they have decision-making capacity. METHODS: The electronic medical records of 240 glioblastoma patients who died between 2017 and 2019 were systematically reviewed for documented SI conversations about four domains (prognosis, goals, end-of-life planning, and code status) using published criteria. Patient outcomes and SI conversation characteristics were analyzed using descriptive statistics. Standardized interviews about glioblastoma care were held with five clinicians. Interview transcripts were analyzed using grounded-theory coding to identify emergent themes. RESULTS: Nearly all patients (96%) had at least one documented SI conversation (median: 4; interquartile range: 2-7), mostly outpatient with oncology physicians. Median timing of first SI conversation was 360 days before death. Prognosis (92% of patients) and goals (89%) were the domains discussed most frequently. SI conversations were not significantly associated with patient outcomes, including inpatient death and hospice enrollment. Seven themes emerged from clinician interviews: balancing hope and reality, anticipatory guidance, neglect of the "big picture, " need for earlier conversations, care coordination, the role of clinical expertise, and communication training. CONCLUSION: SI conversations were documented earlier and more often in our sample than has been previously reported, but their quality was difficult to assess. Contrary to chart review findings, interviewees reported that SI conversations were late, infrequent, and fragmented across specialties, failing to explore issues such as functional prognosis and anticipatory guidance.